Profile of Irregular Antibodies in Multiparous Pregnant Women and Its Implications for Maternal Transfusion Services at Gotong Royong Hospital, Surabaya - Wiwid Salsulhadi Kesehatan; Yustisia Amalia Kesehatan; Miftahul Khairoh (Jurnal Medicare, 2026)
Background: Multiparous pregnancy increases maternal exposure to fetal red blood cell antigens that differ from maternal antigens, potentially triggering the formation of irregular antibodies. These antibodies have implications for maternal transfusion safety because they may complicate the selection of compatible blood and increase the risk of transfusion reactions and hemolytic disease in the fetus or newborn. Objective: This study aimed to identify the profile of irregular antibodies in multiparous pregnant women and analyze their implications for maternal blood transfusion services at Gotong Royong Hospital, Surabaya. Methods: This study employed a descriptive observational design with a cross-sectional approach. The subjects were multiparous pregnant women undergoing antenatal examinations. Laboratory examinations included ABO and Rhesus blood grouping, irregular antibody screening, and antibody identification in samples with positive screening results. Maternal characteristics, parity, transfusion history, and pregnancy history were analyzed descriptively. Results: Variations were found in the results of irregular antibody screening. The identified antibodies were evaluated based on their clinical significance for blood compatibility. Multiparity and a history of blood transfusion were important factors in pre-transfusion evaluation. Conclusion: Screening and identification of irregular antibodies are important to support the selection of compatible blood and improve the safety of maternal transfusion services.